VALIDATION OF NURSING OUTCOMES’ INDICATORS OF NURSING OUTCOMES CLASSIFICATION OF SELF-CARE FOR PATIENTS WITH STROKE - Sri Mulyani; Intansari Nurjannah (Belitung Raya Foundation, Indonesia, 2019)
Background: Evaluation of nursing outcome based Nursing Outcome Classification (NOC) is very important. However, there is dearth of information regarding its validation in Indonesian language. Objective: To validate four nursing outcomes’ indicators of the Nursing Outcome Classification (NOC) for stroke patients with self-care deficit problems. Methods: This was a descriptive quantitative study with cross sectional design. Outcomes indicators of self-care: bathing, dressing, eating, and toileting were developed for measuring its relevance, clarity, simplicity and ambiguity. Content validity index was used for analysis, which involved three nursing experts. Results: Out of the 59 outcome indicators, 49 (83.05%) were considered as passing indicators and 10 (16.95%) were eliminated. Conclusion: The passing indicators can be applied in caring for stroke patients. The NOC indicators can be implemented in clinical setting, particularly for stroke patient with self -are deficit problems.